2012
DOI: 10.1161/strokeaha.111.645713
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function and White Matter Disease in Young Stroke Patients

Abstract: Background and Purpose-Impaired kidney function is thought to be associated with small vessel disease, outcome, and mortality in the general stroke population. Data are limited regarding young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…One reason for this finding could be that our patient cohort was older than that in other studies. 13,15 The link between age and both decreased kidney function and WMD severity is well established. 38 The possible age-related GFR reduction in our cohort could have been understated by the higher age in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this finding could be that our patient cohort was older than that in other studies. 13,15 The link between age and both decreased kidney function and WMD severity is well established. 38 The possible age-related GFR reduction in our cohort could have been understated by the higher age in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, there was no significant association between DM and WMD in studies including >2000 participants after adjustment for confounders. 13,17 Hemoglobin A1c (HbA1c), a biomarker of long-term glycemic control, was not taken into consideration in the aforementioned studies. Few studies conducted in small prespecified cohorts have suggested significant association between levels of HbA1c and WMD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…63 A recent study reported that Fabry patients with the most stable estimated glomerular filtration rate had fewer strokes than those Fabry patients with rapidly progressing renal disease. 64 An analysis of 2500 patients in the Stroke In Young Fabry Patients (SIFAP) study 65 demonstrated that lower estimated glomerular filtration rates within the normal range were associated with the presence of a moderate to severe CWMH load. In this study, increasing severity of CWMH was significantly associated with a lower estimated glomerular filtration rate, 65 raising the possibility that reduced estimated glomerular filtration rates could indicate an increased risk of CWMH and early stroke in patients with FD.…”
Section: Risk Factors Of Ischemic Stroke In Fdmentioning
confidence: 99%
“…64 An analysis of 2500 patients in the Stroke In Young Fabry Patients (SIFAP) study 65 demonstrated that lower estimated glomerular filtration rates within the normal range were associated with the presence of a moderate to severe CWMH load. In this study, increasing severity of CWMH was significantly associated with a lower estimated glomerular filtration rate, 65 raising the possibility that reduced estimated glomerular filtration rates could indicate an increased risk of CWMH and early stroke in patients with FD. Evidence is also emerging of an age-independent association between CWMH load and cardiomyopathy in patients with FD, 66 which may relate to the risk of ischemic stroke.…”
Section: Risk Factors Of Ischemic Stroke In Fdmentioning
confidence: 99%